2019
DOI: 10.4158/accr-2019-0167
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Adrenal Dysfunction After Bilateral Adrenal Infarction: A Case Report

Abstract: Objective: To describe a case of sequential bilateral adrenal infarction and hemorrhage resulting in an unusual pattern of adrenal function over time. Methods: A 50-year-old male with autoimmune antiphospholipid syndrome (APS) presented to the emergency room with severe abdominal pain. Diagnostic studies performed included contrast-enhanced computerized tomographic (IV-CT) imaging of abdomen and pelvis, and laboratory assessment of the hypothalamic-pituitary-adrenal axis. Results: IV-CT of abdomen and pelvis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…These reports all propose that adrenal vein thrombosis is the initial insult to the adrenal gland, especially in the setting of a hypercoagulable state such as antiphospholipid antibody syndrome (APS), followed by hemorrhagic infarction. However, hemorrhage might not always occur [ 5 ]. One case reported the cause of unilateral adrenal infarction in pregnancy to be a complication of APS [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These reports all propose that adrenal vein thrombosis is the initial insult to the adrenal gland, especially in the setting of a hypercoagulable state such as antiphospholipid antibody syndrome (APS), followed by hemorrhagic infarction. However, hemorrhage might not always occur [ 5 ]. One case reported the cause of unilateral adrenal infarction in pregnancy to be a complication of APS [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that this patient already had some degree of depressed adrenal function, and that when compounded by an acute adrenal infarction, had insufficient time for the contralateral adrenal gland to compensate. The acute loss of function of her unilaterally functioning adrenal gland could have led to a substantial enough decline in production capacity to cause an abnormal response to cosyntropin stimulation [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior reports have all suggested that adrenal vein thrombosis secondary to a hypercoagulable state is the initial mechanism leading to adrenal infarction. 12 It may also be related to microvascular thrombosis in the adrenal parenchyma. This is often complicated by haemorrhage due to secondary adrenal necrosis and/or reperfusion injury or anticoagulant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal glands are supplied by multiple arterioles supplied by three main arteries (the inferior phrenic, aorta, and renal artery), whereas there is only a single suprarenal vein to drain the glands. [ 15 ] SARS-CoV utilizes angiotensin-converting enzyme 2 (ACE2) as crucial portals for cellular entry. The virus creates a potential prothrombotic state by causing direct damage to endothelial cells via down-regulation of ACE2 and consequently inhibiting mitochondrial functions.…”
Section: Discussionmentioning
confidence: 99%